Commercial reverse osmosis point-of-use systems in Egypt failed to purify tap water - Mahmoud Gad; Mohamed A. Marouf; Amr Abogabal; Anyi Hu; Noura Nabet (IWA Publishing, 2024)
This study addresses the heightened global reliance on point-of-use (PoU) systems driven by water quality concerns, ageing infrastructure, and urbanization. While widely used in Egypt, there is a lack of comprehensive evaluation of these systems. We assessed 10 reverse osmosis point-of-use systems, examining physicochemical, bacteriological, and protozoological aspects of tap water (inlets) and filtered water (outlets), adhering to standard methods for the examination of water and wastewater. Results showed significant reductions in total dissolved solids across most systems, with a decrease from 210 ± 23.6 mg/L in tap water to 21 ± 2.8 mg/L in filtered water for PoU-10. Ammonia nitrogen levels in tap water decreased from 0.05 ± 0.04 to 2.28 ± 1.47 mg/L to 0.02 ± 0.04 to 0.69 ± 0.64 mg/L in filtered water. Despite this, bacterial indicators showed no significant changes, with some systems even increasing coliform levels. Protozoological analysis identified prevalent Acanthamoeba (42.5%), less frequent Naegleria (2.5%), Vermamoeba vermiformis (5%), and potentially pathogenic Acanthamoeba genotypes. Elevated bacterial indicators in filtered water of point-of-use systems, combined with essential mineral removal, indicate non-compliance with water quality standards, posing a public health concern. Further research on the long-term health implications of these filtration systems is essential. HIGHLIGHTS This is the first study in Egypt to provide a comprehensive assessment of 10 commercial PoUs.; Substantial alteration in physicochemical parameters between tap and filtered water was noticed.; No significant variance in bacterial indicators was observed between tap water and the PoUs' filtered water.; The PoUs remove crucial minerals for human health like magnesium and calcium.; First record of potentially pathogenic V. vermiformis and Acanthamoeba genotypes in the PoUs' filtered water.;